Unconfined Compression Test on In Situ Frozen Clay Sampled from Frozen Wellbore. (8th March 2022) - Wang, Heng; Li, Gongzhou; Ning, Fangbo; Gao, Wei; Su, Bin
Abstract : Based on the current shortcomings in frozen wall designations, in which the unconfined compressive strength test parameters of undisturbed and remolded frozen soils are used for calculations, in situ frozen soil samples were taken from a frozen wellbore, and unconfined compressive strength tests were performed in this study. The test results showed significant discreteness in the in situ freezing uniaxial compressive strength of the cohesive soil, with low test repeatability. Because of the anisotropy of the original soil structure, the elastic modulus of 31.3% of the undisturbed frozen soil was found to be lower than that of the remolded frozen soil at the same temperature, and it was 0.5–2.1 times the elastic modulus of the remolded frozen soil. This value was negatively correlated with the freezing temperature; however, it had no evident relationship with the occurrence depth of the frozen soil. Based on the design principle of the frozen wall of the west air shaft in Zhaogu No. 2 Mine, the thickness calculated by substituting the in situ frozen soil test parameters was 1.14–1.61 times that of the original design of the frozen wall of the viscous soil layer.